BOYCOTTING PRO-ISRAEL PRODUCTS: : Reinventing the Hadith of Tashabbuh in the Contemporary Era - Khamdan, Muh; Ananda, Rifki Abror; Ibnu, Ibnu; Fata, Ahmad Khoirul (ADP Publisher, 2025)
The concept of tasyabbuh is often understood textually by some Muslim groups as a form of resemblance to other groups. This understanding triggers caution to avoid imitating the ways, products, or identities of non-Muslims. However, in an increasingly global cultural context, cross-cultural resemblance becomes inevitable. If not properly understood, the prohibition of tasyabbuh can create difficulties for Muslims themselves. In this context, applying the prohibition of tasyabbuh to the boycott movement of pro-Israel products may become a counterproductive action. This movement encourages the use of alternative products as a form of rejection towards Israel. Interestingly, the availability of these alternative products creates a need to resemble the very products being boycotted. This study uses a qualitative approach with critical discourse analysis methods. The findings reveal that the narrowing of the meaning of tasyabbuh in the context of legal prohibition often overlooks interpretations of cultural resemblance, including in product boycott actions. This article revisits the meaning of the tasyabbuh hadith and relates it to the phenomenon of the boycott of pro-Israel products in the contemporary era.